Research on High Voltage Capacitor Voltage Drop Device. (December 2018) - Zhang, Ling; Ba, Te; Luo, Xiao
Abstract: With the advent of smart grid, smart transmission lines as an important part of smart grid gradually entered the construction. In view of this, installing various testing equipment on the transmission line tower is the basic work of building intelligent transmission line. However, limited by geographical conditions or insulation conditions, there are few low-voltage power supply near the transmission line towers. It is a big problem to supply power to the low-voltage detection equipment on the towers. In this paper, a new method of capacitive buck charging for transmission line towers is proposed. A special high voltage line capacitor and voltage transformer are used in series to extract energy directly from the high voltage line. The insulator string is used as the insulation support of the overvoltage of the transmission line, and the line capacitor and voltage transformer are connected in parallel. Stable energy output is obtained to achieve reliable power supply for transmission line tower monitoring equipment. However, the power supply will inevitably suffer from lightning strikes if it is exposed to nature for a long time. Therefore, it is of great practical significance to study the transient characteristics of Lightning Overvoltage in capacitor power supply system and to study its protection technology to ensure its safe and reliable operation.